INFLUENCE OF THE INTRAVENOUS INFUSION OF COMBINED HYPEROSMOLAR SOLUTIONS ON STRUCTURAL CHANGES IN ORGANS OF NEUROIMMUNOENDOCRINE SYSTEM - Gunas, I.V.; Дзевульська, І.В.; Cherkasov, E.V.; Ковальчук, О.І. (World of Medicine and Biology, 2014)
The article presents data in relation to letalyty, endogenous intoxication and structural changes in adenohypophysis, adrenal cortex and thymus during experimental burn disease in rat under the condition of its treatment by the intravenosis infusion of colloid-hyperosmolar solutions Lactoproteinum-S protects the damage of vessel wall and has a membranoplastic influence on the organic structure.